An Empirical Study on Work- Life Balance Achieved Through Integration (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In this Modern era it is a challenge to get the four aspects of life i.e. Work, health, relationshipand society fall perfectly in place every single day, since priorities keep changing. Work-life balancecreates a competitive and stressful environment for everyone-personally and professionally .That is themyth of work life balance. In this article it focuses on how work life balance is achieved through properintegration and focused less on balancing and more on integrating the different needs of our daily lifeand implementing the best practices on how an organization can implement a successful work-lifeintegration programme which not only facilitates telecommuting along with flexible workingarrangements but also makes the organization an attractive place to work for employees.